Mo‐/Co‐N‐C Hybrid Nanosheets Oriented on Hierarchical Nanoporous Cu as Versatile Electrocatalysts for Efficient Water Splitting - Shi, Hang; Dai, Tian‐Yi; Wan, Wu‐Bin; Wen, Zi; Lang, Xing‐You; Jiang, Qing (Advanced functional materials, 2021)
Designing robust and cost‐effective electrocatalysts based on Earth‐abundant elements is crucial for large‐scale hydrogen production through electrochemical water splitting. Here, nitrogen‐doped carbon engrafted Mo2N/CoN hybrid nanosheets that are seamlessly oriented on hierarchical nanoporous Cu scaffold (Mo‐/Co‐N‐C/Cu), as highly efficient electrocatalysts for alkaline hydrogen evolution reaction are reported. The constituent heterostructured Mo2N/CoN nanosheets work as bifunctional electroactive sites for both water dissociation and adsorption/desorption of hydrogen intermediates while the nitrogen‐doped carbon bridges electron transfers between electroactive sites and interconnective Cu current collectors by making use of Mo‐/Co‐N‐C bonds and intimate C/Cu contacts at interfaces. As a consequence of unique architecture having electroactive sites to be sufficiently accessible, self‐supported nanoporous Mo‐/Co‐N‐C/Cu hybrid electrodes exhibit outstanding electrocatalysis in 1 m KOH, with a negligible onset overpotential and a low Tafel slope of 47 mV dec−1. They only take overpotential of as low as 230 mV to reach current density of 1000 mA cm−2. When coupled with their electro‐oxidized derivatives that mediate efficiently the oxygen evolution reaction, the alkaline water electrolyzer can achieve ≈100 mA cm−2 at 1.622 V in 1 m KOH electrolyte, ≈0.343 V lower than the device constructed with commercially available Pt/C and Ir/C nanocatalysts immobilized on nanoporous Cu electrodes. Heterogenous Mo2N/CoN nanosheets that are in situ engrafted with nitrogen‐doped carbon skin and vertically rooted on nanoporous Cu scaffold (Mo‐/Co‐N‐C/Cu) hold promise as robust and cost‐effective (pre‐)electrocatalytsts for hydrogen/oxygen evolution reactions. Associated with nanoporous architecture to facilitate electron transfer and offer abundant and sufficiently accessible active sites, nanoporous Mo‐/Co‐N‐C/Cu electrodes exhibit oustanding electrocatalytic performance for overall water splitting.